The Role of Culinary Tourism in Shaping Destination Identity and Branding - Nayla Azzahra Ramadhani; Olivia M. Carter; Ethan J. Williams (Tourism and Hospitality Research, 2026)
Culinary tourism has emerged as a strategic component in destination development, contributing significantly to destination identity formation and branding. As tourists increasingly seek authentic and memorable experiences, local gastronomy has become an essential element in differentiating destinations within a highly competitive tourism market. This study aims to examine the role of culinary tourism in shaping destination identity and strengthening destination branding through a systematic review of recent scholarly literature. The study employs a qualitative literature review approach by analyzing contemporary studies published between 2021 and 2025 in reputable tourism and hospitality journals. The findings reveal that culinary tourism contributes to destination branding through five key dimensions: cultural authenticity, heritage preservation, destination image enhancement, tourist engagement, and economic sustainability. Local cuisine functions not only as a tourism attraction but also as a symbolic representation of place identity that strengthens emotional connections between tourists and destinations. Furthermore, effective gastronomic branding strategies improve destination competitiveness, visitor satisfaction, and destination loyalty. The study concludes that culinary tourism has evolved from a complementary tourism product into a core branding asset capable of enhancing destination distinctiveness and long-term sustainability. The findings provide practical implications for destination management organizations, policymakers, and tourism stakeholders seeking to develop competitive and culturally authentic tourism destinations.